Survey Of VO2 Max Levels and Nutritional Status In PB Triple Ten Students Aged 10-12 Years In Kepanjen, Malang District - Khairul Amal; Supriatna Supriatna (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to analyze the results of VO2max levels in students and also the nutritional status of PB Triple Ten aged 10-12 years in Kepanjen, Malang Regency. The research method used is a survey method with a quantitative descriptive approach. The subjects of this research were 15 PB Triple Ten Kepanjen students, Malang Regency. Data collection using bleep test or multistage fitness and body mass index measurements. The results of men's VO2max have an average of 35.7, which is in the (sufficient) category, while the results of women's VO2max have an average of 23.6, which is in the (poor) category. The nutritional status of men has an average of 18.6, including the (normal) category, while the nutritional status of women has an average of 18.1, including the (normal) category. Based on the results of the analysis, it is stated that VO2 max in men is included in the sufficient category while women are still lacking. The nutritional status of men is normal and the same is true for women.